Prediction of the Epidemiological Situation of Tuberculosis in Slovakia by 2040- Data Update - Kober, Lukas; Solovic, Ivan; Littva, Vladimir; Siska, Vladimir (Iranian journal of public health, 2021)
Background: Despite the available diagnostics and treatment, tuberculosis (TB) is a serious infectious disease currently occurring. Even some high-income countries in the world do not fully control it at this time. The reason for this situation is the lack of elimination programs to address the situation. The aim of the update of the prediction data was to create a presumption of TB development in Slovakia by 2040. Methods: We used the time series prediction method with exponential equalization. The basis for the calculation were historical data on the incidence of TB from 1960 to 2018 in Slovakia (data for the last 58 yr). This time series has a clearly declining level. In view of this trend, we have set a threshold, whether and when the incidence in the future will fall below 5.0 patients per 100,000 inhabitants. Results: In case of a favorable development, the limit of our incidence drop below 5.0 cases per 100 000 inhabitants in 2022, when the incidence will be 4.91 per 100 000 inhabitants. In 2040, the predicted incidence of TB should be 1.78 per 100 000 inhabitants. A gradual decline may also be related to a decrease in the population of the Slovak Republic. Conclusion: Slovakia belongs to those countries of the world where TB is under control. Increased surveillance of high-risk communities through community interventions and countries' readiness for global migration can help to influence factors that may aggravate the epidemiological situation of TB.